2020
DOI: 10.1136/jitc-2020-000645
|View full text |Cite
|
Sign up to set email alerts
|

Baseline metabolic tumor volume as a strong predictive and prognostic biomarker in patients with non-small cell lung cancer treated with PD1 inhibitors: a prospective study

Abstract: BackgroundReliable predictive and prognostic markers are still lacking for patients treated with programmed death receptor 1 (PD1) inhibitors for non-small cell lung cancer (NSCLC). The purpose of this study was to investigate the prognostic and predictive values of different baseline metabolic parameters, including metabolic tumor volume (MTV), from 18F-fluorodeoxyglucose positron emission tomography–computed tomography (18F-FDG PET/CT) scans in patients with NSCLC treated with PD1 inhibitors.MethodsMaximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 33 publications
3
66
0
Order By: Relevance
“…This negative correlation of tumor size and ICB sensitivity is borne out in patients where total tumor volume is predictive of response to αPD-1 with local or metastatic melanoma ( 47 , 48 ). In patients with NSCLC, metabolic tumor volume was also a prognostic factor for sensitivity to PD-1 blockade in both retrospective and prospective studies ( 22 , 49 ). Furthermore, dual ICB, which targets both PD-1 and CTLA-4 at the same time, has shown greater efficacy than single ICB in patients with metastatic NSCLC and melanoma ( 40 , 43 ), and is more effective in melanoma patients with smaller baseline tumor diameters ( 50 ).…”
Section: Impact Of Tumor Burden On Therapy-induced Immune Responsesmentioning
confidence: 99%
“…This negative correlation of tumor size and ICB sensitivity is borne out in patients where total tumor volume is predictive of response to αPD-1 with local or metastatic melanoma ( 47 , 48 ). In patients with NSCLC, metabolic tumor volume was also a prognostic factor for sensitivity to PD-1 blockade in both retrospective and prospective studies ( 22 , 49 ). Furthermore, dual ICB, which targets both PD-1 and CTLA-4 at the same time, has shown greater efficacy than single ICB in patients with metastatic NSCLC and melanoma ( 40 , 43 ), and is more effective in melanoma patients with smaller baseline tumor diameters ( 50 ).…”
Section: Impact Of Tumor Burden On Therapy-induced Immune Responsesmentioning
confidence: 99%
“…Several studies have compared PET/CT to CT imaging in monitoring ICI treatment, with results suggesting an additional prognostic value of metabolic response assessments [ 10 ]. The role of pre-ICI 18F-FDG PET/CT scanning has been investigated in some monocentric retrospective studies, with different findings [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have described maximum standardized uptake value (SUVmax) as a potential predictive marker of response to ICIs [ 11 , 15 ], whereas others have not found any correlation [ 12 ]. Metabolic tumor volume (MTV) and total lesion glycolysis (TLG) appear to be the most promising quantitative indexes in predicting the therapy response [ 12 , 13 , 15 ]. A prognostic value for both MTV and TLG has been found in different kinds of malignancies [ 14 , 16 , 17 , 18 ], as demonstrated in previous studies assessing their values at baseline PET [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that inhibiting PD-1/PD-L1 increased the infiltration of CD8+ T cells resulting in the killing of the tumor cells ( Kim et al, 2018 ). PD-1 checkpoint inhibitors such as atezolizumab and nivolumab have been shown to significantly improve the clinical symptoms of patients and prolong survival time in non-small cell lung cancer ( Chardin et al, 2020 ), renal cell carcinoma ( Buchbinder et al, 2019 ), breast cancer ( Szekely et al, 2018 ), and melanoma ( Luke et al, 2017 ). However, Chiu’s study demonstrated that upregulation of PVRL1 inhibited the cytotoxic T cell response through the T-cell immunoglobulin and ITIM domain (TIGIT), thus mediating resistance to PD1 inhibitors in HCC ( Chiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%